The effects of peatland forest ditch maintenance on suspended solids in runoff - Joensuu, S.; Ahti, E.; Vuollekoski, M. (Boreal Environment Research Publishing Board, 2024)
In 1990–1994, the effect of peatland forest ditch maintenance on the concentration of suspended solids in runoff water was studied in Finland in 37 catchments by using a short pre-treatment period and comparing with 31 control areas. On the average, the concentrations of suspended solids were 4–5 mg l–1 in the control areas and in the treatment areas before ditch network maintenance. During a period of 1–3 years after maintenance, the concentration of suspended solids in the water leaving ditch network and entering sedimentation ponds averaged 45.8 mg l–1. The magnitude of the increase depended on the area subjected to ditch maintenance as well as the prevailing soil type at the bottom of the ditches. Measured as 1–3 year averages, only half of the sedimentation ponds reduced the concentration of suspended solids. During the first year after ditch network maintenance, the suspended solids concentration in the water entering the sedimentation ponds averaged 71.3 mg l–1 and the water leaving the ponds 58.1 mg l–1. In the second year, the corresponding values were 26.8 mg l–1 and 21.1 mg l–1 and in the third year, 12.8 mg l–1 and 12.4 mg l–1, respectively.